Cyber law: law of information technology and internet - Rastogi, Anirudh (Gurgaon, 2014)
This book introduces, analyses and provides a comparative critique of the laws governing Information Technology and Cyber- crime in India and book also covers emerging areas of study and concern such as state surveillance, virtual currencies, cloud computing, regulation of social media and appification, website terms and conditions, and e-governance.
Keywords: Cyber law